Analisis Kesiapan Kebijakan Tata Ruang Kota Palu dalam Mendukung Agenda SDG 11 (Kota Berkelanjutan) - Herman, Sitti Rabiatul Wahdaniyah; Takwim, Supriadi; Putri Abdi, Azizah; Rasdiana; Wahyuningsih, Tri (Jurnal Peweka Tadulako, 2025)
This study aims to analyze the readiness of spatial planning policies in Palu City in supporting the achievement of Sustainable Development Goal (SDG) 11, which emphasizes the development of inclusive, safe, resilient, and sustainable cities and human settlements. As a disaster-prone area, Palu City has experienced significant spatial pressures, particularly in the aftermath of the 2018 earthquake, tsunami, and liquefaction events. Utilizing a qualitative descriptive approach and secondary data analysis, this study evaluates spatial planning documents such as the Regional Spatial Plan (RTRW), the Detailed Spatial Plan (RDTR), and the Regional Medium-Term Development Plan (RPJMD) of Palu City for the periods 2016–2021 and 2021–2026. The assessment is based on the alignment of these policies with the key indicators of SDG 11, including the provision of adequate housing, green open spaces, sustainable transportation systems, and disaster risk mitigation. The analysis shows that while SDG 11 principles are reflected in planning documents, their implementation remains limited.. Major challenges include the lack of integrated spatial data, weak inter-agency coordination, and limited community participation in the planning process. Therefore, institutional strengthening, improvements in geospatial data quality, and the mainstreaming of sustainability principles across all sectoral policies are urgently needed. This research contributes to the understanding of the nexus between spatial planning and sustainable development in disaster-prone cities and serves as a reference for future policy improvement.